Analysis of the auto lube system electric grease pump against the unscheduled breakdown of the dump truck unit brand k type HD 1500-7 - Indra Widarmadi; Sahidul Anam; Basuki Wisnu; Husodo Sumardi (JTTM : Jurnal Terapan Teknik Mesin, 2023)
A lubrication failure resulted in damage to the HD 1500-7 dump truck unit auto lube system, making the system ineffective and leading to lubrication failure on the frame components. Because the damaged HD 1500-7 dump truck unit is inoperable when it occurs, this damage may have an impact on its production. The goal of this study was to ascertain whether maintenance performance on the Dump Truck Brand K type HD 1500-7 unit was impacted by lubrication failure in the auto lube system. Additionally, learn how to assess the Auto lube system on the Dump Truck Brand K type HD 1500-7 and how much electricity the Grease Pump Auto lube system Dump Truck unit Brand K type HD 1500-7 uses. Using a quantitative approach, discover what is causing the HD 1500-7 dump truck unit and the auto lube system to malfunction. The analysis of the Dump Truck HD 1500-7 unit's maintenance performed from February to April 2022 revealed that the average MTBF value is 352.9 hours, the average MTTR value is 5.388 hours, and the average PA value is 96.38%. The oil-powered reciprocating pump produces 537.81 Watts of power. At a grease pressure of 2500 psi, the displacement (grease) pump requires 163.29 Watts from the reciprocating (oil) pump to operate, compared to 58.67 Watts at a grease pressure of 1500 psi. The standard working pressure for the displacement (grease) pump is 2500 psi, whereas the standard working pressure for the reciprocating (oil) pump is 400 psi. The working pressure on the oil and grease does not achieve the standard pressure, an error arises and results in lubrication failure in the frame components, and this might have an impact on the HD 1500-7 unit's maintenance performance